Effect of the 345 °C and 16.5 MPa autoclave corrosion on the oxidation behavior of Cr-coated zirconium claddings in the high-temperature steam. (15th August 2021) - Liu, Haiyong; Feng, Yajie; Yao, Yirong; Li, Bingsheng; Wang, Renda; Shi, Xiaoguang; Li, Peng; Shu, Jie; Huang, Feng; Huang, Qing; Ge, Fangfang
Highlights: Enhanced corrosion and oxidation resistances of Zr claddings by the Cr coatings. Effect of the autoclave corrosion on the high-temperature steam oxidation. High oxidation resistance remained in the Cr-coated Zr claddings after corrosion. The pre-corrosion would suppress forming bubbles and cracks in the Cr2 O3 scale. Abstract: Cr-coated Zirlo tubes were conducted in the autoclave corrosion (345 °C and 16.5 MPa), followed by the 1200 °C steam oxidation. After the 1-h oxidation, the coated tubes exhibited structural integrity, in contrast to the uncoated ones that had broken into pieces. Moreover, the coated tubes that already underwent the 45-days pre-corrosion, still remained good oxidation resistance with the weight gain of ∼4.46 mg/cm 2 . During the pre-corrosion, very thin Cr2 O3 tissue formed on the outmost surface and along the columnar boundaries, which would suppress the formation of bubbles and cracks in the subsequent oxidation.